The artistry of symbols and allegories in the prose of Isajon Sultan - Hasanov , Suhrob Shavkat o‘g‘li (The Lingua Spectrum, 2026)
Isajon Sultan’s prose displays a number of features, such as intertextuality, which we emphasize in our article, the multi-level structure of the text, the rhizome (the type of plot as a symbolic labyrinth with a certain center around an axis that does not stick together), including the death of the traditional author’s point of view (narrative chaos). However, the author’s work differs from postmodernist works by a number of features, such as the fact that it grew on the soil of strong national traditions, that it creates metanarratives, and does not turn to the methods of “play” and “theater”, characteristic of postmodernism.